Navigating the Immune Response Landscape of Hepatitis B and Hepatitis C Virus Infections - Hammood, Saja Qasim; Mahmood, Ellaf Abdulljabbar Jassim prf. Dr. Alia Essam; Kadhem, Ashwaq A. (Journal of Medical Genetics and Clinical Biology, 2024)
Both the hepatitis B virus (HBV) and the hepatitis C virus (HCV) are viral pathogens that primarily target the liver and can lead to chronic liver disease. The nature of the immune response that the host mounts can vary depending on the structural differences between these two viruses. HBV is a partially double-stranded DNA virus enveloped in an outer envelope with a relatively stable genome and limited antigenic variation. It consists of an inner nucleocapsid core containing viral DNA, viral polymerase, and core antigen (HBcAg). The envelope comprises surface antigens (HBsAg) important for viral entry and immune recognition. HCV is a single-stranded RNA virus with an envelope. It has a high degree of genetic diversity due to its error-prone RNA polymerase, resulting in multiple HCV genotypes and subtypes due to its high mutation rate. Both viruses activate innate immune responses, producing type I interferons (IFNs) and pro-inflammatory cytokines. HBV can actively fight these antiviral responses in several ways, such as by making viral proteins that mess up the innate immune signalling pathways. At the same time, HCV developed strategies to evade and modulate the host's innate immune system, allowing it to establish persistent infections. The adaptive immune response against HBV and HCV involves both humoral and cellular components. Antibodies against HBsAg (anti-HBs) are critical for viral clearance and protection. CD8+ T cells are also very important for controlling HBV infection because they find and kill infected hepatocytes. During infection, HCV-specific antibodies and CD4+ and CD8+ T cells are made. However, HCV can evade immune responses by rapidly mutating its surface proteins (e.g., E2) and modulating T-cell responses. It is important to note that the immune response to HBV and HCV is a complex and dynamic process that involves various factors beyond the structural differences described above. Host factors, viral load, viral persistence, and the interplay between innate and adaptive immune responses also significantly influence the outcome of the infection